MAKNA FILOSOFIS MOTIF SENI UKIR REK PALEMBANG - Hudaidah, Hudaidah; Trianti, Lilis; Rukmana, Lisa (Panggung, 2023)
The wood carving motifs of Palembang, known as “rek,” have been a traditional craft since the eraof Srivijaya and continue to endure to this day. This craftsmanship holds high philosophical valuesinfluenced by Hindu-Buddhist and Islamic cultures. Its uniqueness lies in the predominant use of goldenyellow color, and its carvings are exceptionally distinctive. The purpose of this writing is to unveil thephilosophical meanings embedded in the motifs of Palembang’s wood carvings. The central issue is toexplore the philosophical meanings of these motifs in Palembang’s wood carvings. This study employs ahistorical research method, with heuristic, source criticism, interpretation, and historiography steps. Thetradition of wood carving art exhibits distinct characteristics and the uniqueness of various motifs, eachcarrying different philosophical values. The research findings indicate that the various motifs found inPalembang’s wood carvings hold profound philosophical meanings. For example, the motif of buddingbamboo shoots symbolizes that humans should be beneficial to others, and the golden color representstriumph. Therefore, it is crucial to preserve this heritage for the younger generation so that they candevelop an appreciation for their local culture, strengthen personal values, and enhance their identity,and self-awareness.Keywords: Philosophical Meaning, Motif, Wood Carving, Typical of Palembang